The effects of physical activity across curriculum (PAAC) on academic achievement, body mass index and cognitive performance among 10 years old - Fakri, Noor Fatin Nazieffa (2018)
Introduction: Physical Activity Across Curriculum (PAAC) can give beneficial effect to the students. This study was designed to examine the effect of PAAC on academic achievement, body mass index and cognitive performance among school students. Objective: To determine whether Physical Activity Across Curriculum (PAAC) affect academic achievement (Mathematic), body mass index, and cognitive performance (short-term memory) among 10 years old students. Methods: Fifty six primary school students aged 10 years old were recruited and being assigned into two groups, with twenty eight participants per group (n=28): physical activity across curriculum (PAAC) and non-physical activity across curriculum (non PAAC) groups. PAAC were carried out 60 minutes per week, 2 sessions, and 30 minutes per session for 7 weeks. Subjects who were involved in physical activity played selected activities such as jumping, running and walking. The non PAAC group were taught via traditional classroom method. Results: At post test, there was no significant (p>0.05) difference in academic achievement (Mathematic test score) in PAAC and non PAAC. Mathematic test score increased in post test compared to pre test in PAAC and NON PAAC groups. The percent increase of mathematic test score in PAAC group was higher (+27.60%) thannon PAAC (+15.42%). There also was no significant (p>0.05) difference in BMI in PAAC group. The percentage change in PAAC group was -2.56%. The percent increase of BMI in non PAAC group was +0.86%. There was no significant changes in cognitive performance (digit span test). However, the percent increase of digit span test in PAAC group was higher (+43.39%) than non PAAC (+19.57%). Conclusion: Physical activity across curriculum (PAAC) has potential to be proposed for formulating guidelines in planning exercise promotion programmes for increasing academic achivement, body mass index and cognitive performance in participants aged 10 years old.